Motherisk Update - Shapiro, Lori (1998)
QUESTION: One of my patients conceived while using a topical tretinoin preparation for acne. I know this drug is related to Accutane, which is teratogenic. How should I advise her? ANSWER: Available evidence suggests that topical tretinoin does not increase teratogenic risk in humans.